2015
DOI: 10.1517/14728222.2015.1056154
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin receptor subtype 3 as a potential target for obesity and diabetes

Abstract: Summary Introduction Diabetes mellitus and obesity are important health issues; increasing in prevalence, both in the US and globally. There are only limited pharmacological treatments, and although bariatric surgery is effective, new effective pharmacologic treatments would be of great value. This review covers one area of increasing interest that could yield new novel treatments of obesity/diabetes mellitus. It involves recognition of the central role the G-protein-coupled receptor, bombesin receptor subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 122 publications
(376 reference statements)
3
53
0
Order By: Relevance
“…In the present study, we found that peptide antagonist Bantag-1 had a high affinity for BB 3 receptor as reported previously [14,15] and high selectivity for BB 3 receptor, with a >30,000-fold higher affinity for BB 3 receptor over BB 2 or BB 1 receptor, despite the fact that these receptors share an 51 and 47% amino acid identity, respectively [1,32]. To investigate this in detail, a chimera receptor approach was initially used substituting extracellular domains of BB 3 receptor (high affinity, Bantag-1) with those from BB 2 receptor (low affinity, Bantag- 1) resulting in potentialaBantag-1 loss-of-affinity chimeras.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we found that peptide antagonist Bantag-1 had a high affinity for BB 3 receptor as reported previously [14,15] and high selectivity for BB 3 receptor, with a >30,000-fold higher affinity for BB 3 receptor over BB 2 or BB 1 receptor, despite the fact that these receptors share an 51 and 47% amino acid identity, respectively [1,32]. To investigate this in detail, a chimera receptor approach was initially used substituting extracellular domains of BB 3 receptor (high affinity, Bantag-1) with those from BB 2 receptor (low affinity, Bantag- 1) resulting in potentialaBantag-1 loss-of-affinity chimeras.…”
Section: Discussionsupporting
confidence: 87%
“…These studies and others provide evidence that, similar to the other BnRs (i.e. BB 2 receptor /BB 1 receptor), BB 3 receptor is important in regulation of feeding/satiety[34] in addition to regulation of various behaviors, glucose and insulin homeostasis, as well as metabolic homeostasis, and may play an important role in diabetes and obesity [3,13,15,29,30,32,33]. However, BB 3 receptor selective antagonists/agonists would be invaluable to further investigate BB 3 receptor role in these and other areas.…”
Section: Introductionmentioning
confidence: 99%
“…BRS-3 expression has been noted in multiple tumor types (lung carcinoma, carcinoid, renal cell, Ewing sarcoma, pancreatic, pituitary, ovarian, prostate) [1]. Since the tissues from which the cancers originate typically express little BRS-3, some tumor cells may upregulate BRS-3 expression.…”
Section: Other Possible Physiological Rolesmentioning
confidence: 99%
“…Bombesin-like receptor 3 (BRS-3, also known as bombesin receptor subtype 3 and BB 3 ) is an orphan X-linked Gq-coupled receptor [1]. BRS-3 was named for its sequence similarity to receptors binding bombesin, a 14-amino acid frog peptide.…”
mentioning
confidence: 99%
See 1 more Smart Citation